2020
DOI: 10.21203/rs.3.rs-47538/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between haematological parameters and sickle cell genotypes in children with Plasmodium falciparum malaria resident in Kisumu County in western Kenya

Abstract: Background: Sickle cell disease (SCD) is a monogenic disorder due to point mutation in the β-globin gene resulting in substitution of Valine for Glutamic acid. The SCD is prevalent in P. falciparum endemic regions such as western Kenya. Carriage of different sickle cell genotypes may influence haematological parameter during malaria. Children resident in malaria holoendemic regions suffer more from malaria-related complications and this is moderated by the presence of the SCD. In the current study, we determin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The participants included in the study were divided into four groups according to their sickle cell phenotypes (HbSS, HbSC, HbAS, HbAC and HbAA), and no significant difference in mean age was found, underlining the efficacy of the clinical management of children with SCD at the YUH (13, 50–54). As already reported, parasitaemia and haemoglobin levels at inclusion were lower in sickle cell patients with major forms than in patients with normal phenotype (5558). This low parasite density could be an element explaining a protective effect against severe malaria.…”
Section: Discussionsupporting
confidence: 82%
“…The participants included in the study were divided into four groups according to their sickle cell phenotypes (HbSS, HbSC, HbAS, HbAC and HbAA), and no significant difference in mean age was found, underlining the efficacy of the clinical management of children with SCD at the YUH (13, 50–54). As already reported, parasitaemia and haemoglobin levels at inclusion were lower in sickle cell patients with major forms than in patients with normal phenotype (5558). This low parasite density could be an element explaining a protective effect against severe malaria.…”
Section: Discussionsupporting
confidence: 82%
“…Haematological changes or abnormalities are some of the most common complications in malaria and they play a major role in malaria pathogenesis [27,28]. Previous studies have reported that haematological parameters are affected by P. falciparum infection and mutations in the HBB gene [19,29,30]. The presence of the sickle cell mutation has been shown to in uence malaria outcome in populations where the infection is endemic [31] such as western Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on prevalence of sickle cell trait in the study area [20] using Cochran's formula [21]. The details of the study population are described in details in our previous publication [19].…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations